Novel type of adenylyl cyclase participates in tabtoxinine-β-lactam-induced cell death and occurrence of wildfire disease in Nicotiana benthamiana - Ito, Makoto (Landes Bioscience, 2014)
Tabtoxinine-β-lactam (TβL), a non-specific bacterial toxin, is produced by Pseudomonas syringae pv. tabaci, the causal agent of tobacco wildfire disease. TβL causes the plant cell death by the inhibiting glutamine synthetase, which leads to an abnormal accumulation of ammonium ions. To better understand the molecular mechanisms involved in TβL-induced cell death and necrotic wildfire lesions, we focused on adenylyl cyclase in Nicotiana benthamiana. We isolated the gene designated as NbAC (Nicotiana benthamiana adenylyl cyclase). Recombinant NbAC protein showed adenylyl cyclase activity in vitro. TβL-induced necrotic lesions were significantly suppressed in NbAC-silenced leaves compared with control plant leaves. However, the amount of ammonium ions was scarcely affected by NbAC-silencing. Furthermore, the silencing of NbAC also suppressed l-methionine sulfoximine-induced cell death without any changes in the amount of ammonium accumulated. When inoculated directly with P. syringae pv tabaci, NbAC-silenced plants showed reduced symptoms. These results suggest that NbAC might play an essential role in intracellular signal transduction during TβL-induced cell death and necrotic wildfire disease development.